Study of collinear cracks in a composite medium subjected to time-harmonic wave disturbance - Trivedi N.; Das S.; Altenbach H. (My University, 2025)
The article deals with the collinear Griffith cracks under the time-harmonic waves, situated in an orthotropic strip sandwiched between two identical half-planes. The outer cracks are considered to be situated on either sides of the central crack. The mathematical model is solved by applying the Fourier transform and then the unknown functions have been determined using Schmidt method. The approximate analytical expressions of the stress intensity factors (SIFs) have been obtained at the tips of the cracks. The values of the SIFs for the considered composite with Graphite epoxy material as the strip and E-glass epoxy as the half-plane are computed numerically for different crack lengths and wave numbers, and the obtained results are displayed graphically. The salient feature of the article is the pictorial presentations of the possibilities of arrest of the central crack due to the presence of outer cracks through finding the stress magnification factor for different particular cases. © 2021 Wiley-VCH GmbH